2018
DOI: 10.3389/fnins.2018.00199
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Stem Cell Models of Alpha-Synuclein Gene Regulation in Neurodegenerative Disease

Abstract: Alpha-synuclein (non A4 component of amyloid precursor, SNCA, NM_000345.3) plays a central role in the pathogenesis of Parkinson's disease (PD) and related Lewy body disorders such as Parkinson's disease dementia, Lewy body dementia, and multiple system atrophy. Since its discovery as a disease-causing gene in 1997, alpha-synuclein has been a central point of scientific interest both at the protein and gene level. Mutations, including copy number variants, missense mutations, short structural variants, and sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 169 publications
(211 reference statements)
2
20
0
Order By: Relevance
“…Additionally, SNCA was significantly downregulated after p-value combination in MSA-C (adj p < 0.05). The same result was found in another study [30], but not confirmed in other work [28,42]. Other studies based on oligodendrocyte isolation and qPCA analysis described a basal expression and a trend of an increased expression in MSA patients [4,19].…”
Section: Discussion Overviewsupporting
confidence: 73%
“…Additionally, SNCA was significantly downregulated after p-value combination in MSA-C (adj p < 0.05). The same result was found in another study [30], but not confirmed in other work [28,42]. Other studies based on oligodendrocyte isolation and qPCA analysis described a basal expression and a trend of an increased expression in MSA patients [4,19].…”
Section: Discussion Overviewsupporting
confidence: 73%
“…α-syn (encoded by SNCA, NM_000345.3, OMIM *163890) is a key protein in the pathogenesis of PD and related α-synucleinopathies [120]. Since its discovery as the first PD-causing gene in 1997 [121][122][123], several missense mutations, a number of risk SNPs, small structural variants (SSV), and, recently, cases with SNCA multiplications and somatic mosaicism have been described [9,124,125]. Genomic duplications and triplications of various genomic sizes of the 4q22.1 genomic region are highly penetrant and contribute to PD, LBD, or multiple system atrophy (MSA).…”
Section: Snca Genomic Region (4q221) Is Multiplication/deletion Syndmentioning
confidence: 99%
“…Genomic duplications and triplications of various genomic sizes of the 4q22.1 genomic region are highly penetrant and contribute to PD, LBD, or multiple system atrophy (MSA). The critical genomic region of these cases spans the SNCA gene, which is the only gene overlapping in all described cases [9,[125][126][127]. While earlier studies used single PCR-based copy number analysis, comparative genomic hybridization (CGH) and optical mapping can now define the size of CNVs, breakpoints, and orientation much more accurately [128] (Figure S1, Table S3C).…”
Section: Snca Genomic Region (4q221) Is Multiplication/deletion Syndmentioning
confidence: 99%
“…Because of the genetic background of α-synucleinopathies, research must also be focused toward discovering the exact molecules and mechanisms for posttranscriptional and epigenetic regulation of SNCA gene. Up to this point, it is established that not only changes in the gene sequence (multiplications, missense mutations, and single nucleotide polymorphisms) but also activation of certain transcriptional factors and RNAs may affect α-Syn regular expression [38]. MicroRNAs (MiRNAs) are small non-coding RNA molecules encoded as independent genomic transcription units predominantly engaged as regulators of protein expression mostly through inhibition of mRNA translation or cleavage [39,40].…”
Section: Regulation Of α-Synuclein Expressionmentioning
confidence: 99%